2016
DOI: 10.1002/2015ja022138
|View full text |Cite
|
Sign up to set email alerts
|

Dust acoustic dromions in a magnetized dusty plasma with superthermal electrons and ions

Abstract: An investigation of dust acoustic (DA) dromions in a magnetized dusty plasma consisting of inertial dust fluid, kappa‐type distributed electrons, and ions is presented. Using reductive perturbation technique, we have derived coupled nonlinear evolution equations of (2 + 1) dimensions (called Davey‐Stewartson (DS‐I) equations). Hirota bilinear method has been employed to derive the analytical solution of DS‐I equations. The solutions of such equations are exponentially localized and are called dromions. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Earlier works have shown that the above system (DS-II) occurs in relation with ion acoustic (Nishinari et al 1993) and dust-ion acoustic (Xue 2004) plasmas. On the other hand, DS-I occurs in (un)magnetized dust acoustic (Duan 2004;Saini et al 2016) and electron acoustic (Sen et al 2004) plasmas, etc. Those systems sustain dromion solutions which, rather counter-intuitively, cannot exit in our model.…”
Section: Perturbative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier works have shown that the above system (DS-II) occurs in relation with ion acoustic (Nishinari et al 1993) and dust-ion acoustic (Xue 2004) plasmas. On the other hand, DS-I occurs in (un)magnetized dust acoustic (Duan 2004;Saini et al 2016) and electron acoustic (Sen et al 2004) plasmas, etc. Those systems sustain dromion solutions which, rather counter-intuitively, cannot exit in our model.…”
Section: Perturbative Analysismentioning
confidence: 99%
“…Typical plasma parameters corresponding to planetary rings for dusty plasma are: 0 = (10 13 − 10 16 ) −3 , 0 = (10 13 − 10 16 ) −3 , = 10 3 , = 10 13 −3 , = 50 eV, = 0.05 eV (Goertz 1989). Modulated wavepackets are ubiquitous in space; however, the generalization of the standard theory for modulational processes (Kourakis & Shukla 2005) to higher dimensionality (Davey & Stewartson 1974;Nishinari et al 1993Nishinari et al , 1994Fokas & Santini 1989;Duan 2004Duan , 2003Sen et al 2004;Xue 2004;Saini et al 2016) is not entirely understood. The transverse perturbations are supported by higher dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…The associated particles are then called the superthermal particles as a result of the extreme amount of energy the particle acquired. [9] Vasyliunas [23] was the first to introduce the kappa distribution function with the spectral index . To explain its relation with the Maxwellian distribution, let → ∞.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,6,7 ] Dust acoustic (DA) mode is one of these eigenmodes that has been initiated theoretically in unmagnetized plasma by Rao et al [ 1 ] and later it has been verified experimentally by Barkan et al [ 8 ] Few decades ago, it was theoretically investigated that the dust acoustic wave (DAW) is present in an electron‐ion‐dust plasma. [ 9 ] Several space observations have emphasized the presence of nonlinear features in space domain. Later, these observations were interpreted by Seyler et al [ 10 ] by formulating one‐dimensional model for the detected solitary waves and by studying the corresponding steady state wave solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation